PRESTASI BELAJAR SISWA SMPN 01 BANTAN KABUPATEN BENGKALIS - Diana, Salasia; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in the District Bantan SMPN1 Bantan Bengkalis on 04 May till 04 August 2011, in which is the object of this study were students SMPN1 Bantan who have high achievement in school . This study was conducted aimed to determine the extent of student achievement and the factors that influence student achievement , in this study researchers looked only at class VIII course consisting of 3 classes each class of 10 respondents taken 3 classes so over all there were 30 respondents. to obtain accurate data , the researcher used purposive sampling of data retrieval intentionally , koesioner data collection form . This research is a descriptive study in which data is collected and arranged beforehand according to the nature and classified according to the type of data to be analyzed. The survey results revealed bahawa factors that affect student achievement are internal factors ( desire achievement of students , the level of intelligence of the students ) . and external ( family environment that includes how to educate children , young large families , family income , parental education level , family economic circumstances . neighborhood school which includes school supplies , teacher student relationship , the relationship between parents and the school and community environment or a friend to play . could be seen from the achievements of students each follow evaluations most students who have high achievement scored 80-95 , a total of 12 respondents ( 40 % ) , achievement was the value obtained is 7.0 -7.9 , as many as 10 respondents ( 33.33 % ) , and students with low achievement scores â‰¤ 6.9 each evaluation consists of 8 respondents ( 26.67 % ) . achievement is good followed by the availability of adequate learning tool . factors that affect student achievement is the major internal factors which include the desire of the student achievement , and intelligence factors from within the student . desire high achieving students SMP 01 Bantan based study consisted of 9 respondents , from 9 respondents who had achievements height is 6 respondents ( 66.67 % ) and a proven record of being composed of three respondents ( 33.33 % ) . intelligence students also affect student performance in school . Factors affecting student achievement is not only internal factors but there are external factors behind student achievement in school , external factors include : family environment and school environment . Keywords : Student Achievement, external factors, internal factors,